2021
DOI: 10.1007/s13238-021-00832-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the phase separation characteristics of nucleocapsid protein provides a new therapeutic opportunity against SARS-CoV-2

Abstract: Understanding the phase separation characteristics of nucleocapsid protein provides a new therapeutic opportunity against SARS-CoV-2 Dear EditorTo date, tens of millions of people have been infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causing the outbreak of the respiratory disease named the coronavirus disease 2019 . As a newly emerged member of the coronavirus family, SARS-CoV-2 is an enveloped positive-strand RNA virus, which has probably the largest genome (approximately 30 k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 14 publications
3
49
0
Order By: Relevance
“…The importance of LLPS in vivo in the viral life cycle is stressed by results from an evolutionary analysis of SARS-CoV-2 (Gussow et al, 2020), which found localization in the nucleolus, a macromolecular condensate ll OPEN ACCESS iScience Article of proteins and RNA, and is correlated with increased pathogenicity and case fatality rate. LLPS may be regulated by small molecules, and is thereby susceptible to small molecule inhibitors, some of which have already been identified in different laboratories (Carlson et al, 2020;Cubuk et al, 2021;Iserman et al, 2020;Jack et al, 2020;Zhao et al, 2021). We believe this strategy of therapeutic development will be supported by increasing detailed knowledge of molecular configurations and binding processes involved in N-protein functions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance of LLPS in vivo in the viral life cycle is stressed by results from an evolutionary analysis of SARS-CoV-2 (Gussow et al, 2020), which found localization in the nucleolus, a macromolecular condensate ll OPEN ACCESS iScience Article of proteins and RNA, and is correlated with increased pathogenicity and case fatality rate. LLPS may be regulated by small molecules, and is thereby susceptible to small molecule inhibitors, some of which have already been identified in different laboratories (Carlson et al, 2020;Cubuk et al, 2021;Iserman et al, 2020;Jack et al, 2020;Zhao et al, 2021). We believe this strategy of therapeutic development will be supported by increasing detailed knowledge of molecular configurations and binding processes involved in N-protein functions.…”
Section: Discussionmentioning
confidence: 95%
“…Structures and dynamics of both CTD and NTD, isolated or in complex with NA, have been studied and reveal significant molecular details (Ahamad et al, 2020;Caruso et al, 2020;Chen et al, 2007;Dinesh et al, 2020;Kang et al, 2020;Takeda et al, 2008;Zinzula et al, 2020). Intriguingly, it was reported recently by several laboratories that N-protein undergoes liquid-liquid phase separation (LLPS) (Carlson et al, 2020;Cascarina and Ross, 2020;Chen et al, 2020a;Cubuk et al, 2021;Iserman et al, 2020;Jack et al, 2020;Lu et al, 2021;Perdikari et al, 2020;Savastano et al, 2020;Wang et al, 2021;Zhao et al, 2021). Such demixing is commonly mediated by ultra-weak but highly multi-valent interactions (Alberti et al, 2019;Vernon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Multi-stimuli-responsive carriers (thermal or pH-responsive reversible coacervate droplets) can also be imbued with the ability to package and deliver drugs ( Gabryelczyk et al, 2019 ). Furthermore, microfluidic techniques can be employed to create monodisperse coacervate droplets, making it possible to mimic diverse intracellular activities within uniform unilamellar lipid vesicles ( Deshpande et al, 2001 ; Van Swaay et al, 2015 ; Deng and Huck, 2017 ; Love et al, 2020 ; Zhao et al, 2021 ). However, the intrinsic properties and functions of these coacervate droplets may differ dramatically as a function of size, and it remains unclear how large a condensate must grow before specific functions can arise ( Lyon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shortly after the emergence of SARS-CoV-2, we proposed that the SARS-CoV-2 N protein would undergo PS in vitro, and that similar biophysical behavior in vivo might mediate the formation of RNA-protein condensates during viral RNA packaging into new virions, or modulate host-cell condensates (namely, stress granules) via direct physical interaction (19). In the ensuing months, many studies examining various aspects of the PS behavior of the SARS-CoV-2 N protein, including its role in viral RNA packaging, stress granule modulation, regulation of host-cell innate immune pathways, and regulation by host-cell kinases, were formally published (7,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).…”
Section: Ps and The Sars-cov-2 N Proteinmentioning
confidence: 99%
“…PS of proteins is often sensitive to salt concentrations and types of salts used (48), which is generally presumed to reflect electrostatic driving forces for PS. Lower salt concentrations were typically associated with enhanced N-protein PS (20,25,28,29,32,33,35,36), suggesting that electrostatic interactions play an important role in PS. Additionally, in the few studies that examined N-protein PS across a range of pH conditions, lower pH was associated with enhanced PS (20,32).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%